2015
DOI: 10.7249/rr784
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the Careers of Military Spouses: An Assessment of Education and Employment Goals and Barriers Facing Military Spouses Eligible for MyCAA

Abstract: This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to duplicate this document for personal use only, as long as it is unaltered and complete. Permission is required from RAND to reproduce, or reuse in another form, any of its research documents for commercial use. For information on reprint and linking permissions, please… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…For married soldiers, Work/Life Balance challenges may also include intrusions into spouses' educational opportunities and careers, which can be disrupted by such features of military life as frequent permanent change of station (PCS) moves, international assignments, deployments and other geographic separations, and long work hours, or need to care for wounded spouses (Segal, 1986;Sticha et al, 1999;Drummet, Coleman, and Cable, 2003;Booth, Segal, and Bell, 2007;Castaneda and Harrell, 2008;Cooney, De Angelis, and Segal, 2011;DMDC, 2013;Blue Star Families, 2014;Ramchand et al, 2014;Friedman, Miller, and Evans, 2015; Defense Manpower Data Center and U.S. Department of Defense, Office of the Deputy Assistant Secretary of Defense for Military Community and Family Policy, 2015).…”
Section: Work/life Balancementioning
confidence: 99%
“…For married soldiers, Work/Life Balance challenges may also include intrusions into spouses' educational opportunities and careers, which can be disrupted by such features of military life as frequent permanent change of station (PCS) moves, international assignments, deployments and other geographic separations, and long work hours, or need to care for wounded spouses (Segal, 1986;Sticha et al, 1999;Drummet, Coleman, and Cable, 2003;Booth, Segal, and Bell, 2007;Castaneda and Harrell, 2008;Cooney, De Angelis, and Segal, 2011;DMDC, 2013;Blue Star Families, 2014;Ramchand et al, 2014;Friedman, Miller, and Evans, 2015; Defense Manpower Data Center and U.S. Department of Defense, Office of the Deputy Assistant Secretary of Defense for Military Community and Family Policy, 2015).…”
Section: Work/life Balancementioning
confidence: 99%
“…While we do not have an experimental framework, we argue that our results can be causal given our implementation of a propensity score matching framework in which we can control for service members' career profiles. Furthermore, we argue that unobservable information plays a minimal role, given that a previous analysis of survey data found that spouses who had used MyCAA in the previous 12 months (spanning 2011 to 2012) were no more likely to support the service member continuing than comparable past year nonusers (Friedman, Miller, and Evans, 2015), further indicating that any impact of MyCAA on spousal support for service member continuation is not immediately realized but may develop later, during or after the use of MyCAA Scholarship funds. Furthermore, the measured impact is positive even among the population of households whose service members continue in active service beyond the end of the three-year scholarship window, suggesting service members did not remain in the service to allow the spouse to complete his or her program.…”
Section: Discussionmentioning
confidence: 80%
“…While we do not directly observe the education levels of eligible individuals, MyCAA provides funding only for associate's degrees or occupational certificates and licenses, meaning that many users are likely to have less than a bachelor's degree. Indeed, in the 2012 Active Duty Spouse Survey (ADSS), 84 percent of spouses who had used MyCAA in the past year held less than a bachelor's degree (Friedman, Miller, and Evans, 2015). Along those lines, we show that the impact on retention was larger when MyCAA was used for an associate's degree, as compared with an occupational certificate.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations